A Case Study of Tariq Road Underpass, Karachi: Environmental Analysis - Abbasi, Haq Nawaz; Khan, Rubina; Nasir, Imran; Ahmad, Waqar (International Journal of Economic and Environmental Geology, 2023)
The construction projects are rising in Pakistan to overcome the flow of traffic on the main road of big cities. Karachi is the metropolitan city of Pakistan facing uncontrolled growth and urbanization, which leads to an increase in the demand for urban transport facilities. The study focuses on the assessment of the environmental impacts of the Tariq Road underpass construction site. The data was collected with the help of community consultation using analytical methods. It includes public chat, site visits, interviews, questioners, and the samples collection of environmental components. The results show that the most common hazards were related to excavation, working practice variation, and personal protective equipment (PPEs). Faulty and unmaintained machinery with the lack of proper barrier producing noise and air pollution.